Inhibition of Epithelial TNF-α Receptors by Purified Fruit Bromelain Ameliorates Intestinal Inflammation and Barrier Dysfunction in Colitis - Zhou, Zijuan; Wang, Liang; Feng, Panpan; Yin, Lianhong; Wang, Chen; Zhi, Shengxu; Dong, Jianyi; Wang, Jingyu; Lin, Yuan; Chen, Dapeng; Xiong, Yongjian; Peng, Jinyong (Frontiers in Immunology, 2017)
Activation of the TNF-α receptor (TNFR) leads to an inflammatory response, and anti-TNF therapy has been administered to reduce inflammation symptoms and heal mucosal ulcers in inflammatory bowel disease (IBD). Bromelain, a complex natural mixture of proteolytic enzymes, has been shown to exert anti-inflammatory effects. This study aimed to investigate the effect of purified fruit bromelain (PFB)-induced inhibition of epithelial TNFR in a rat colitis model. Colitis was established by intracolonic administration of 2, 4, 6-trinitrobenzene sulfonic acid. Expression of TNFR1 and TNFR2 was measured by quantitative RT-PCR and western blotting. The effect of PFB on colitis was evaluated by examining the inflammatory response and intestinal epithelial barrier function. Our results showed that both TNFR1 and TNFR2 expression were significantly increased in a colitis model, and the increase was significantly reversed by PFB. Colitis symptoms, including infiltration of inflammatory cells, cytokine profiles, epithelial cell apoptosis, and epithelial tight junction barrier dysfunction were significantly ameliorated by PFB. Compared with fruit bromelain and stem bromelain complex, the inhibition of TNFR2 induced by PFB was stronger than that exhibited on TNFR1. These results indicate that PFB showed a stronger selective inhibitory effect on TNFR2 than TNFR1. In other words, purification of fruit bromelain increases its selectivity on TNFR2 inhibition. High expression of epithelial TNFRs in colitis was significantly counteracted by PFB, and PFB-induced TNFR inhibition ameliorated colitis symptoms. These results supply novel insights into potential IBD treatment by PFB.